Plano de projeto: desenvolvimento e implantação de um controle de demandas no setor de desenvolvimento da empresa - Santos, Camila Kolling dos (Universidade do Vale do Rio dos Sinos, 2016)
This work aims to create a project plan for the development and implementation of a control demands on the Company's development of sector X. The result of the implementation of the planned project should be a standardized and automated demand distribution flow, able to assist the development area manager to monitor the demands on your manages, facilitating corrections of stocks and improving the delivery time of the solution to customers. To prepare the project plan were created management plans in the areas of integration , scope, time , cost, risk , human resources, quality , communication , stakeholders and acquisitions, using the best practices of the 4th edition of the PMBOK
Keywords: Controle de demandas; Plano de gerenciamento do projeto; PMBOK; Demand control; Project management plan